Exploring Cultural Differences in the Extent to Which People Perceive and Desire Control. (January 2019) - Hornsey, Matthew J.; Greenaway, Katharine H.; Harris, Emily A.; Bain, Paul G.
In a seminal theory piece, Weisz and colleagues argued that control over one's environment was less attainable and desirable in Japan than in America. Subsequently, many scholars have extrapolated from this argument to claim broad-based cultural differences in control: that Western/individualist cultures perceive and desire more personal control over their environment than do Eastern/collectivist cultures. Yet surprisingly little empirical research has put this claim to the test. To test this notion, in Study 1 we examined perceived control over one's life in 38 nationally representative samples ( N = 48, 951). In Study 2, we measured desire for control in community samples across 27 nations ( N = 4, 726). Together, the studies show lower levels of perceived and desired control in Japan than in any other nation. Over and above the Japan effect, there was no evidence for differences in perceived or desired control between individualist and collectivist nations, or between holistic and nonholistic nations.